Silibinin Inhibits ICAM-1 Expression via Regulation of N-Linked and O-Linked Glycosylation in ARPE-19 Cells. (17th June 2014) - Chen, Yi-Hao; Chen, Ching-Long; Liang, Chang-Min; Liang, Jy-Been; Tai, Ming-Cheng; Chang, Yun-Hsiang; Lu, Da-Wen; Chen, Jiann-Torng
Abstract : To evaluate the effects of silibinin on intercellular adhesion molecule-1 (ICAM-1) expression, we used ARPE-19 cells as a model in which tumor necrosis factor (TNF- α ) and interferon (IFN- γ ) enhanced ICAM-1 expression. This upregulation was inhibited by silibinin. In an adherence assay using ARPE-19 and THP-1 cells, silibinin inhibited the cell adhesion function of ICAM-1. The inhibitory effects of silibinin on ICAM-1 expression were mediated via the blockage of nuclear translocation of p65 proteins in TNF- α and phosphorylation of STAT1 in IFN- γ -stimulated cells. In addition, silibinin altered the degree of N-linked glycosylation posttranslationally in ARPE-19 cells by significantly enhancing MGAT3 gene expression. Silibinin can increase the O-GlcNAc levels of glycoproteins in ARPE-19 cells. In a reporter gene assay, PUGNAc, which can also increase O-GlcNAc levels, inhibited NF- κ B reporter activity in TNF- α -induced ARPE-19 cells and this process was augmented by silibinin treatment. Overexpression of OGT gene was associated with reduced TNF- α -induced ICAM-1 levels, which is consistent with that induced by silibinin treatment. Taken together, silibinin inhibits ICAM-1 expression and its function through altered O-linked glycosylation in NF- κ B and STAT1 signaling pathways and decreases the N-linked glycosylation of ICAM-1 transmembrane protein in proinflammatory cytokine-stimulated ARPE-19 cells.